KORYO-SARAM: THE FORMATION OF A DIASPORA THROUGH FORCED ETHNIC RELOCATION AND ITS SOCIO- CULTURAL TRANSFORMATION IN CENTRAL ASIA (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the historical and social processes that shaped the Koryo-saram population throughout the 20th century. It examines issues related to the policy of forced resettlement implemented during the Soviet period. Particular attention is given to the status of Koryo-saram as a diaspora and to the social functions of the Korean language across different historical periods. Based on available empirical data, the processes of everyday life and social adaptation of Koryo-saram are examined within a broader context. In addition, social, cultural, and institutional developments of the post-Soviet period are taken into account.
Keywords: forced ethnic relocation; post-deportation identity; linguistic shift process; Soviet Koreans; stateless diaspora concept